Metastatic signet ring cell adenocarcinoma of the bladder: - Singh, Jessica; Zherebitskiy, Viktor; Grynspan, David; Czaykowski, Piotr Marek (Canadian Urological Association Journal, 2013)
Signet ring cell variant of mucinous adenocarcinoma of the urinary bladder is an exceptionally rare urologic malignancy, generally felt to be resistant to chemotherapy and radiotherapy. We describe a case of this malignancy with unusual sites of metastasis and an unexpectedly good response to treatment.